Silent augmented narratives: Inclusive Communication with Augmented Reality for deaf and hard of hearing - Berra,Susanna (2020)
Deafness is an often undervalued but increasing problem amongst the worlds population. Besides the difficulty in hearing sounds, it involves many cognitive and emotional issues, like learning difficulties, isolation, and disempowerment. In this paper, the design of artifacts for deaf people is analyzed from two different perspectives: Technology and Communication Science. Regarding technological issues, research shows how Augmented Reality can be applied using screen interfaces or smart glasses translating sounds into visual stimuli; looking at the communication possibilities, the focus is on storytelling and how it can be combined with the technology used to engage people, enhance learning activity and create a community. By looking into these two aspects, the suggested approach is to merge them in a conceptual creative project that can be appealing and useful to the public, through the use of interactive storytelling, while also using the visual benefits of an immersive Augmented Reality experience.